Success and failure rates of new food and non-food products introduced on the market - Ireneusz P. Rutkowski (Journal of Marketing and Consumer Behaviour in Emerging Markets)
Theoretical and empirical research reveals that despite implementing new product development and management best practices, many projects fail with new product strategies. But what if failure rates as high as 90% are true? This would mean that high costs of product innovation are incurred by many stakeholders who create a specific network of relationships, not just enterprises. The widespread belief that the new product failure rate is 90% is not supported by empirical evidence. The aim of the paper is to present the real market eff ects of new products, success and failure rates, from the point of view of food and non-food companies representing various industries. The research measures in the field of marketing and sales eff ects of new products are also proposed. The method used in this paper is a literature review in the area of new product development and management. The author assumes that the review and conceptual nature of this research isdominant. Practical and social implications of the study, its originality concerns the results that provide the basis for the improvement of enterprises’ eff orts in the field of a new product strategy. The limitations of the study include a complex character of considered theoretical constructs and they also concern the used secondary data sources on which the considerations in the article are based. The values of the paper refl ect the directions of enterprises’ conduct in the new food and nonfood product development process. Failure and success rates are in fact diffi cult to quantify. The research contribution to marketing sciences primarily includes the formulation of a set of real success and failure rates in food and non-food industries.